Perancangan Sistem Repositori Digital Berbasis Web untuk Pengelolaan Publikasi pada Kesatuan Press - Yanto Hermawan; Sinta Listari; Meilani Kizana (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
This research aims to design a web-based digital repository system to optimize the management of scientific publications at Kesatuan Press. The main problem currently faced is the management of publication data which is still conventional, making it difficult to search, store, and disseminate information efficiently. The proposed solution is the development of a centralized digital platform with automated archiving features and high accessibility. The system development methodology uses the Waterfall model which includes requirements analysis, design, coding, and testing. The results of the study indicate that the implementation of this digital repository is able to improve the administrative order of publications and facilitate authors and readers in accessing scientific works online. This system is expected to be the main supporting infrastructure for Kesatuan Press in increasing the visibility of academic publications.